Hubungan Status Gizi, Panjang Badan Lahir Dan Pemberian Asi Eksklusif Dengan Kejadian Stunting Pada Anak Usia 24-59 Bulan Di Kecamatan Medan Belawan - Khoirunnisa M.J. Harahap; Mila Trisna Sari (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Introduction: The incidence of stunting in North Sumatra Province reached 25.8% and is the 17th province with the incidence of stunting in Indonesia. Stunting in Medan City is spread across 63 urban villages and 20 sub-districts with the area that has the highest stunting rate is Medan Belawan Sub-district. Purpose: This research was conducted to assess the relationship between nutritional status, birth length and exclusive breastfeeding with the incidence of stunting in children aged 24-59 months in Medan Belawan District in 2023. Method: This research uses an observational study research design with a cross sectional design approach. carried out in the work area of ​​the Medan Belawan District Health Center. The sample was children aged 24-59 months who were recorded at the Medan Belawan District Health Center in 2023 who met the inclusion and exclusion criteria during the research period with a total sample of 44 people. Results: A total of 5 children (29.4%) with good nutrition experienced stunting, 11 children (68.8%) with poor nutrition experienced stunting and 11 children (100.0%) with poor nutrition experienced stunting with a p-value of 0.001. A total of 4 children (33.3%) with normal birth length experienced stunting and 22 children (59.4%) with short birth length experienced stunting with a p-value of 0.002. As many as 10 children (45.5%) who received exclusive breast milk experienced stunting and as many as 17 children (77.3%) who did not receive exclusive breast milk experienced stunting with a p-value of 0.030, which means p-value < 0.005. Conclusion: There is a significant relationship between nutritional status, birth length and exclusive breastfeeding with the incidence of stunting in children aged 24-59 months in Medan Belawan District in 2023.